Individual investor portfolio performance in retirement savings accounts. (November 2015) - Gan, Su (Sally); Heaney, Richard; Gerrans, Paul
We analyse the investment performance of a large sample of individuals investing in discretionary superannuation products offered by a large Australian financial institution. We do not find gender differences as has previously been reported but we do find evidence of a negative relationship between investor age and performance. Those residing in wealthier postcodes perform better. In terms of investment characteristics, wholesale investors perform better whereas those who are the most active perform worse.